Conductivity of polymethylmethacrylate filled with carbon black or carbon fibres under oscillatory shear - Krückel, Johannes; Stary, Zdenek; Triebel, Christian; Schubert, Dirk W.; Münstedt, Helmut (Polymer, 2012)
The electrical conductivity of polymer composites containing conductive fillers is strongly influenced by the structure of the particle network. Therefore, the change of this network under deformation in the molten state is of great interest, in order to obtain materials with desirable electrical properties. In this work polymethylmethacrylate containing carbon black or carbon fibres was exposed to oscillatory shear deformations and the electrical conductivity of the materials was measured simultaneously. It was found that the particle networks in the composites filled with carbon fibres were more sensitive to deformation than those of the carbon black composites. The stability of the networks increased with growing amount of fillers. Furthermore, it could be shown that conductive and rheological networks behave completely different under shear deformations.
Keywords: Polymer composites; Rheology; Conductivity